(untitled) (CAHIERS MAGELLANES-NS, 2024)
Metal-based homeopathic medicines have long been used in homeopathic practice, yet skepticism remains regarding their efficacy, safety, and scientific credibility. This review assesses the evidence surrounding these remedies, examining their therapeutic potential, safety concerns, mechanisms of action, and clinical applications. Despite historical use, evidence of efficacy for metal-based homeopathic medicines is inconclusive, with conflicting study results and reliance on anecdotal evidence. Challenges in research include formulation variability and lack of standardized protocols. Safety concerns arise due to potential metal toxicity and insufficient reporting of adverse events. Proposed mechanisms of action involve the transfer of vibrational energy, but scientific frameworks struggle to reconcile this concept. Recent research methodologies offer opportunities for better understanding. Specific metal-based remedies, including Arsenicum album, Ferrum metallicum, and others, are discussed for their traditional uses and therapeutic properties. The metal-based homeopathic medicines pose a unique and controversial aspect of alternative medicine. Further evidence-based research and interdisciplinary collaboration are crucial to determining their role in healthcare integration.